Demobilization and Reintegration Programs : Addressing Gender Issues - Nathalie de Watteville (World Bank, Washington, DC, 2012)
Women have always participated to some extent in combat, but several recent wars have seen them fighting on the front lines. And while the roles of female excombatants vary widely, the women seem to share one unfortunate characteristic: limited access to benefits when peace and demobilization come. This is also true for girls abducted for sexual services and the families of ex-combatants in the receiving community. These groups are often neglected during demobilization and reintegration; or at best, women, men, boys, and girls may receive equal benefits but are treated as a homogenous group, which prevents their specific needs from being addressed. Some think that the first objective of a DRP (Demobilization and Reintegration Program) is to have a positive impact on the peace dividend. Another goal often mentioned is the reduction of military expenditures for budgetary reasons. However, others argue that the DRP objectives should be to assist vulnerable excombatans.